Why nations fail : the origins of power, prosperity and poverty / Daron Acemoglu and James A. Robinson - Acemoglu, Darson (London, 2013)
What makes one nation successful in obtaining wealth, prosperity and power, while another nation succumbs to poverty? Is it the cultural differences, economic institutions, geography, or other factors? Why Nations Fail: The Origins Of Power, Prosperity And Poverty is a non-fiction book that attempts to give reasons for the economic rise or fall of a nation. Handling one of the intriguing topics in economics, authors Daron Acemoglu and James A. Robinson have put in their insight in bringing up an interesting perspective on the factors governing the economical wellbeing of a nation. The book uses the vision from the concepts of institutional economics, development economics and economic history. The concepts deal with understanding of human evolution and institutions, economic aspects of low income countries and economic phenomena of the past. Based on an original research for fifteen years, the authors have collected wide information from various historical civilizations. The research led to an understanding of the conditions and evolution of economy and politics. This helped the authors in coming up with a theory that entwines politics and economy in reasoning the prosperity and poverty of nations.
Keywords: Economic anthropology